Suppression of Interictal Epileptic Activity by AEDs - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
Rates of full suppression of interictal epileptiform activity were compared for phenobarbital (PHB), carbamazepine (CBZ), and valproate (VPA), in a study at Tufts University School of Medicine, Boston, MA.